Examining Digital Technology Literacy of Professional Japanese Language Translator and Interpreter - Fatmawati Djafri; Lufi Wahidati (Lingua Cultura, 2022)
The research measured the digital technology literacy skills of professional Japanese language translators and interpreters. A modified version of the digital literacy skills checklist constructed by Open University was employed in the research. The questionnaire consisted of four sections, i.e., understanding general digital practices, finding, using, and creating information related to Japanese translation and interpreting, and the use of translation and interpreting technology. The result shows that respondents have confidence in their digital literacy skills to find, use, or create information online. However, most of them are still unfamiliar with the application of Computer Assisted Translation (CAT) and Computer Assisted Interpreting (CAI) tools to assist the translation or interpreting jobs. The result indicates that many Japanese businesses and industries do not require translators and interpreters to use specific CAT or CAI tools. However, the rapid development of digital technology and the market trend toward the use of technology are inevitable. Basic knowledge of these tools is necessary because they offer many advantages for translators and interpreters to work effectively. Therefore, it is highly important to incorporate the basic knowledge of CAT and CAI tools and other digital technology resources into the curriculum for students translators and interpreters.